PENGARUH STRUKTUR CORPORATE GOVERNANCE DAN KEPUTUSAN KEUANGAN TERHADAP KEBIJAKAN DEVIDEN DAN NILAI PERUSAHAAN - Triwulan, Heni; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2012)
The purpose of this study is to test whether the constitutional ownership, managerial ownership,board size, funding decisions and investment decisions and dividend policy affect the value of thecompany. The results of this study show that: (1) Institutional Ownership positive effect ondividend policy ; (2) Managerial ownership has a positive effect on dividend policy ; (3) The size ofthe board of commissioners has no effect on dividend policy ; (4) The funding decision does notaffect the dividend policy ; (5) The investment decision positive effect on dividend policy ; (6)Institutional Ownership positive effect on the value of firms ; (7) Managerial ownership negativelyaffect the value of the company ; (8) Size commissioners positive effect on firm value ; (9) Thedecision of funding has a positive effect on firm value ; (10) The investment decision does not affectthe value of the company ; (11) Devidend policy has no effect on firm value.Key words : institutional ownership , Managerial Ownership , funding decisions , investmentdecisions , dividend policy , the value of the company .